PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Rany Gesta Putri Rais; Nur Afni Yunita; Muhammad Yusra (LPPM Universitas Malikussaleh – Indonesia, 2023)
This study aims to determine the effect of profitability, leverage, company size, institutional ownership and capital intensity on tax avoidance in multinational companies in the mining sector listed on the Indonesia Stock Exchange in 2018-2020. The sample selection technique used was purposive sampling and obtained 15 companies as samples. The data analysis method used is multiple linear regression analysis. The results of this study indicate that partially profitability, leverage, firm size and capital intensity have no effect on tax avoidance, while institutional ownership affects tax avoidance in multinational companies in the mining sector listed on the IDX in 2018-2020